Chip breaking by triangular tool path in turning process - Shogo NAKAMURA; Kenji OHARA; Kenichi NAKANISHI; Naohiko SUGITA (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
In turning processes, effective chip control is crucial for preventing machining issues such as tool damage, workpiece surface defects, and equipment malfunctions caused by cutting chips. This paper introduces a novel chipbreaking method using a triangular tool path to enhance chip management without compromising surface quality. The technique involves creating a triangular motion in the cutting tool, enabling intermittent air cuts that effectively break chips. This approach can be implemented easily by modifying existing CNC programs, without requiring specialized tools or equipment. Experimental results show that the proposed method successfully breaks continuous chips into smaller segments, significantly reducing chip-related risks. Surface roughness remained comparable to conventional turning, demonstrating that this method preserves surface quality. However, a drawback of the triangular tool path is the increased machining time due to extended tool movement. To mitigate this, higher feed rates were applied during rough-cutting stages, reducing machining time without affecting surface roughness or roundness. This study highlights the potential of a triangular tool path as a practical solution for chip control in unmanned and automated machining environments. Although further optimization is needed to improve machining time, this method offers a flexible and cost-effective option for enhanced chip management.